Vpliv popolne gibalne neaktivnosti na psihično zdravje in počutje zdravih mladih preiskovancev - Dolenc, Petra (Zdravstveno varstvo, 2008)
Objective: The aim of the study was to examine the effects of prolonged physical inactivity on the subject's level of anxiety, emotional regulation and control, and concentration ability. Methods: Horizontal bed rest (BR) is a well-accepted method to simulate an acute stage of human adaptation to the microgravity in space flights, and also an important model to study consequences of physical inactivity and sedentarism on human body. The subjects participating in the study were ten healthy male volunteers, aged between 20 and 25, who were exposed to a 35-day horizontal BR in strict hospital environment. The participants were asked to complete psychometrical inventories - the State Anxiety Inventory, the Emotional Regulation and Control Scale and the Test of Concentration and Achievement - prior to, during and after the BR experiment. Results: After the period of physical immobility no significant decrease in the examined psychological variables was established. The level of anxiety, emotional regulation and control, and concentration ability, expressed as the quantity of achievement, remained relatively stable during the experiment, whereas concentration expressed as the quality of achievement even improved after the experiment (p=0.020). Conclusion: Research results showed no adverse effects of prolonged physical immobility on the psychological state of the selected group of subjects. We tried to identify possible reasons for the established findings, and to compare them with the results of similar previous studies. The findings are applicable to the health and sport areas.
Keywords: duševno zdravje; gibalna aktivnost; mental health; neaktivnost